El goce inefectivo del derecho a la salud en el Vaupés : una mirada desde la observación No. 14 del Comité de Derechos Económicos, Sociales y Culturales y los Determinantes Sociales de la Salud (2017)
In order to raise awareness and generate a reflection on the reality of the indigenous population of the department of Vaupús, this document aims, firstly, to publicize the situation of violation of the fundamental right to health of this specific group. Specifically, it seeks to show the materialization of the violation through the lack of articulation and initiative between the public policies of different sectors. This lack of articulation results in a vulnerable and forgotten department in the satisfaction of their fundamental rights. In order to comply with these objectives, the investigation will show the reality of the health situation in the department. This, through indicators in health and the approach that was made in the judicial visit performed by the Constitutional Court in attention to an action of protection in health interposed by the Defensor del Pueblo...